Sesonal variations in exposure to methylmercury and its dietary sources among pregnant Inuit women in Nunavik, Canada - de Moraes Pontual, Mariana; Ayotte, Pierre; Little, Matthew; Furgal, Chris; Boyd, Amanda D.; Muckle, Gina; Avard, Ellen; Ricard, Sylvie; Gauthier, Marie-Josée; Anassour-Laouan Sidi, Elhadji; Lemire, Mélanie (Science of The Total Environment, 2021)
Among populations living in close connection with the sea, rivers and lakes for subsistence, diet varies according to local monthly wildlife species availability and food preferences. This may lead to variations in methylmercury (MeHg) exposure over a year, although no biomonitoring studies have documented this issue in Circumpolar populations, the most exposed to international Hg emissions. Our aim was to characterize seasonal variations in MeHg exposure among pregnant Inuit women from Nunavik and to identify country foods responsible for these variations. Between October 2016 and March 2017, 97 participants were recruited. Blood mercury (Hg) was tested and hair Hg was measured by centimeter as a surrogate for monthly MeHg exposure over the past year. Latent class growth analysis was conducted to identify groups of pregnant women with similar hair Hg monthly trajectories. Country foods consumption was documented by season. Seasonal daily intakes of MeHg were estimated based on concentrations in country foods. Retrospective monthly hair Hg analyses revealed that MeHg exposure was lowest in winter, and highest in summer and early fall months. Three latent classes (groups) of pregnant women with similar trajectories of monthly hair Hg variations were identified: high (n = 20, 21%), moderate (n = 38, 41%) and low variation (n = 35, 38%). Beluga meat was the country food contributing to most of daily MeHg intake, primarily during summer and fall, and was the only one associated with the odds of being classified into moderate and high variation groups (OR 95% CI: 1.19 [1.01–1.39] and 1.25 [1.04–1.50]). These findings underscore the importance of monthly variations in exposure to MeHg due to the seasonality of local foods consumed and responsible for elevated MeHg exposure. Further studies critically need to understand local diet fluctuations over a year to adequately assess MeHg exposure, adopt timely preventive interventions and evaluate the effectiveness of the Minamata Convention. The NQN project was funded by ...